Fuzzy logic-PLC-based controller for water treatment simulator system - Dewi, Astrie Kusuma; Labatar, Gilbert; Hamdani, Chalidia Nurin; Wardhana, Asepta Surya (Politeknik Negeri Lhokseumawe, 2024)
The constant demand for clean water is critical for both consumption and daily activities. A water pH control system is essential for regulating and determining the concentration of acid and base values in water. Research projects often employ a Programmable Logic Controller (PLC) control system with various control methods. This serves as the backdrop for the design of a water treatment simulator, which utilizes a fuzzy logic control system. Fuzzy logic control is a reliable method that produces effective and accurate output values. Experiments conducted on the designed water treatment simulator demonstrate this. Factors influencing the relationship between the solution pump response time and the normalized water pH results are the concentrations of the pH-UP and pH-DOWN solutions. The water treatment simulator is a lab-scale water pH control system simulation tool using a fuzzy logic control mode. It uses an Outseal PLC microcontroller, a pH sensor to measure pH, a DC pump, and a solenoid valve to control the output flow. The experimental results show a significant relationship between the initial pH value of the water measured and the response time of the solution pump. Data analysis shows a positive correlation where the further the pH concentration value of the water is from the normal pH state, the higher the response time value. Factors influencing the relationship between the solution pump response time and the normalized water pH results are the concentration of the pH UP and pH DOWN solutions. The concentration of the solution is set for a pH UP of 12.2 and a pH DOWN solution of 2.2.